Answer to ECG Quiz no. 21 - Okreglicki, A (SA Heart Journal, 2017)
There is second degree heart block with the atrial rate double the ventricular rate. The atrial rate is fast: Possibly an atrial tachycardia but more likely a sinus tachycardia in a sick patient.